2003
DOI: 10.1124/mol.63.6.1349
|View full text |Cite
|
Sign up to set email alerts
|

Thiol-Modifying Phenylarsine Oxide Inhibits Guanine Nucleotide Binding of Rho but Not of Rac GTPases

Abstract: Phenylarsine oxide (PAO) is a phosphotyrosine phosphatase inhibitor that cross-links vicinal thiol groups, thereby inactivating phosphatases possessing XCysXXCysX motifs. The RhoAGTPase, but not the Rac1-GTPase, also possesses vicinal cysteines within the guanine nucleotide-binding region (aa [13][14][15][16][17][18][19][20] and the phosphohydrolase activity site. Treatment of Caco-2 cells with PAO showed a dose-dependent reorganization of the actin cytoskeleton, indicating involvement of Rho GTPases. As teste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 22 publications
3
45
0
Order By: Relevance
“…7 and 8). PAO preferentially reacts with closely spaced (vicinal) thiol groups in proteins to form stable, sulfur-metal ring complexes, and its targets include protein Tyr phosphatases (Carballo et al, 1999), vesicle trafficking, and associated proteins (Arien et al, 2003;Gerhard et al, 2003), as well as inducible NO synthase (Oda et al, 2000). A feature of PAO complexes is their lability to reduction by BAL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 and 8). PAO preferentially reacts with closely spaced (vicinal) thiol groups in proteins to form stable, sulfur-metal ring complexes, and its targets include protein Tyr phosphatases (Carballo et al, 1999), vesicle trafficking, and associated proteins (Arien et al, 2003;Gerhard et al, 2003), as well as inducible NO synthase (Oda et al, 2000). A feature of PAO complexes is their lability to reduction by BAL.…”
Section: Discussionmentioning
confidence: 99%
“…In mammalian tissues, PAO targets protein Tyr phosphatases (Carballo et al, 1999) through its ability to oxidatively bridge critical Cys, and it also affects other protein-signaling intermediates, including human syntaxin 1A (Arien et al, 2003) and Rho GTPases (Gerhard et al, 2003). In guard cells, PAO has been reported to counter the effects of ABA, dark, and H 2 O 2 in closing stomata and to promote stomatal opening, at least in part through its effect on tonoplast ion transport (MacRobbie, 2002), and to affect ABA-mediated gene expression (Heimovaaradijkstra et al, 1996).…”
Section: Pao Mimics No Suppression Of I Koutmentioning
confidence: 99%
“…PAO forms cyclic dithiaarsenane adducts with thiols in X-C-X-X-C-X motifs to irreversibly inactivate many cellular signaling molecules (30)(31)(32)(33)(34). We thus exploited its membrane permeability and reactivity on vicinal cysteines (while sparing free monothiols) to dissect TRPV1 modulation.…”
Section: H2o2mentioning
confidence: 99%
“…PAO can crosslink vicinal thiol groups and is a known phosphatase inhibitor. 135 Treatment of human colonic Caco-2 cells with PAO exhibited a dose-dependent reduction in actin stress fibers, a phenotype consistent with reduced RhoA activity. Moreover, pull-down experiments revealed a PAO concentration-dependent decrease in the levels of GTPbound RhoA.…”
Section: Redox Regulation Of Rhoamentioning
confidence: 99%
“…The authors performed nucleotide dissociation and association assays in vitro and observed a loss of nucleotide binding in RhoA but not Rac1 upon exposure to PAO. 135 Mass spectrometry revealed that PAO crosslinked 2 vicinal cysteines in RhoA to occlude nucleotide binding. These effects were specific to RhoA but not Rac1 as only Rho GTPases (RhoA, RhoB, RhoC, and RhoE) possess vicinal cysteines (Cys 16 and Cys 20 ) within the guanine nucleotide-binding region.…”
Section: Redox Regulation Of Rhoamentioning
confidence: 99%